Clinical outcome of high-grade cervical intraepithelial neoplasia during pregnancy: A 10-year experience. (May 2019) - Hong, Da Kyung; Kim, Seon Ah; Lim, Kyung Taek; Lee, Ki Heon; Kim, Tae Jin; So, Kyeong A
Abstract: Objective: To investigate the clinical outcome of high-grade cervical intraepithelial neoplasia (CIN) diagnosed by colposcopy-directed biopsy during pregnancy and to evaluate the risk factors for persistent disease. Study Design: This retrospective study included pregnant women who were diagnosed with CIN2+ by colposcopy-directed biopsy from January 2005 to December 2014. The clinical characteristics, histopathologic results, and human papillomavirus (HPV) test results were reviewed. The final histopathologic result after delivery was compared with the initial diagnosis to determine disease progression, persistence, or regression. Results: During the 10-year period, 215 pregnant women were diagnosed with high-grade CIN (75 CIN2, 140 CIN3) by colposcopy-directed biopsy. The mean age of the patients was 30.4 years. A total of 187 patients (87.0%) had high-risk HPV infections, with 76 (35.3%) infections identified as HPV genotype 16 or 18. Excisional procedures for diagnosis and treatment were not performed during pregnancy. The histopathologic results of 160 patients (normal in 43, CIN1 in 10, CIN2 in 15, CIN3 in 89, and invasive cancer in 3) were evaluated during the postpartum period. Multivariate logistic regression analysis was performed, and postpartum high-risk HPV infection (OR 5.09; 95% CI 2.15–12.05; P < 0.001) was identified as a significant independent predictor of CIN2+ persistence. Conclusions: Conservative management of CIN2-3 during pregnancy is acceptable. However, persistent high-risk HPV infection is a major risk factor for CIN2+ persistence. Close follow-up with HPV testing, and postpartum colposcopy evaluation are necessary.